2016
DOI: 10.1037/met0000068
|View full text |Cite
|
Sign up to set email alerts
|

A taxonomy of path-related goodness-of-fit indices and recommended criterion values.

Abstract: Almost all goodness-of-fit indexes (GFIs) for latent variable structural equation models are global GFIs that simultaneously assess the fits of the measurement and structural portions of the model. In one sense, this is an elegant feature of overall model GFIs, but in another sense, it is unfortunate as the fits of the 2 different portions of the model cannot be assessed independently. We (a) review the developing literature on this issue, (b) propose 6 new GFIs that are designed to evaluate the structural por… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
72
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(77 citation statements)
references
References 49 publications
3
72
2
Order By: Relevance
“…For example, in the most extreme cases models with six and five paths incorrectly omitted had one or more mean global fit values that would lead to favorable evaluation. This pattern of results was replicated by Lance, Beck, Fan, and Carter (2016). In terms of real data, McDonald and Ho (2002) were the first to investigate empirically, and they found that in 14 studies from top psychology journals reporting adequate information for analysis, nearly all demonstrated acceptable global fit, but only a few yielded adequate path model fit.…”
Section: Comments Recommendations and Future Directions For Conditiomentioning
confidence: 79%
See 1 more Smart Citation
“…For example, in the most extreme cases models with six and five paths incorrectly omitted had one or more mean global fit values that would lead to favorable evaluation. This pattern of results was replicated by Lance, Beck, Fan, and Carter (2016). In terms of real data, McDonald and Ho (2002) were the first to investigate empirically, and they found that in 14 studies from top psychology journals reporting adequate information for analysis, nearly all demonstrated acceptable global fit, but only a few yielded adequate path model fit.…”
Section: Comments Recommendations and Future Directions For Conditiomentioning
confidence: 79%
“…Its empirical performance was supported in a simulation study by Williams and O’Boyle (2011), who found that the RMSEA-P successfully distinguished between correctly and incorrectly specified models in all but one example that was atypical in that it was based on a small number of indicators per latent variable. More recently, Lance et al (2016) reported less positive findings for the RMSEA-P, describing that with their simulation study the RMSEA-P values for moderately misspecified models (three true paths omitted) were less than .08, which would lead to these models being retained. More positive results for the RMSEA-P have been found by Williams and Williams (2017), who first reanalyzed data from Lance et al and reached a more favorable assessment.…”
Section: Steps For Improved Theory Testing and Model Evaluationmentioning
confidence: 94%
“…To summarize, we evaluated whether 2016-2017 Behavior Genetic papers met the standard for best practice (5%), better practice (50%), and acceptable practice (72.5%). Very few papers met the best standard (Appelbaum et al, 2018;Lance et al, 2016;, which recommended that multiple indices across classes (parsimonious, relative, and absolute) be used in conjunction with the χ² statistic. We believe that these recommendations are both generous and reasonable across all SEM models.…”
Section: Discussionmentioning
confidence: 99%
“…Within the context of structural equation modeling, the guidelines for best practice are broad (Appelbaum et al, 2018;Lance et al, 2016;. For evaluating model fit, best practice recommends that multiple indices across classes be used in conjunction with the χ² statistic.…”
Section: Best Practices For Evaluating Model Fitmentioning
confidence: 99%